Euphemism Uttered by March Sisters in Little Women (2019) Film - Munawwarah, Alfina; Rahayu, Famala Eka Sanhadi; Sudirman, Eka Pratiwi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2024)
This research aims to describe the euphemism uttered by March Sisters in Little Women (2019) film, focusing on what types of euphemisms and what the functions of euphemisms appear in the film with a sociolinguistic approach using Burridge (2012) theory. The researcher then displays the findings qualitatively. The result of this research shows that, the March Sisters; Jo, Meg, Amy, and Beth used thirty six euphemisms including eight different types of euphemism out of fifteen; metaphor, underestimate, hyperbole, ellipsis, circumlocution, affixation, rhyming, and external borrowing. Meanwhile, for the functions, March Sisters used all six functions of euphemism; protective, underhand, uplifting, provocative, cohesive, and ludic. Jo is the most user of metaphor because she frequently used a non-literal sentences. Jo mostly used euphemism to protect the listener’s feeling as she is an empathetic person. Amy, as the spoilest one, she is the most underestimate user. She used it to avoid some existing fact, which is to protect herself from feeling embarrassed. Beth used metaphor and hyperbole, but for the function, she used it all as a protective euphemism to protect the listener’s feeling because all of her euphemism words are related to dead, she died in the film caused by scarlet fever. Meg is the least euphemism user. She only use hyperbole twice and circumlocution once but all of them used as a protection to her self-esteem because she is easy to be provoked. In conclusion, March Sisters used euphemism differently based on their personality.